Communication moderate influences motivation and leadership, motivation, discipline work towards performance - Pribadi Widyatmojo, Dwi Fatmawati dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Employees are important aspects to achieve of reaching company objective. Company has to payattention to leadership, motivation, discpline work, and communication variables, in order to increaseemployee performance. Leaders with positive attitude towards the employees enhance employeeâs selfconfidence to excute company job. Employees that receive leaderâs attention will execute the company jobdiscipline without any pressure.The aim of this research is to explore the influence of leadership, motivation, discipline workand communication variable towards employee performance of Limited Company Taspen ( Persero) whichhas 39 employees. This research is explaining exactly the influence of leadership, motivation, disciplinework toward the company employee performance.This research used regression technique to dig up influence of the independent variables. Thisresearch supports the conclusion that motivation and discipline work influence significantly on employeeperformance, motivation influence significantly on discipline work and leadership doesnât significantly onemployee performance and motivation, communication is not moderation on motivation at LimitedCompany Taspen (Persero) Yogyakarta.Keywords:[Leadership, Motivation, Disipline Work, Communication, Employes Performance]